Fostering an element of culture in Singapore’s preschool education: The implementation of mother tongue language - Liu, Yi-Yi; Chiang, Wen-Wei; Lin, Chia-Fen; Chiang, Yu-Ming; Shih, Yi-Huang (Edelweiss Applied Science and Technology, 2025)
In the process of learning multiple languages, children are exposed to different cultural backgrounds and modes of communication, which not only enhance their language proficiency but also foster their understanding and respect for cultural diversity. At the same time, this learning process helps children develop critical thinking and problem-solving skills, as they need to switch and adapt between different languages and cultures. Moreover, multilingual learning promotes social connections, enabling children to interact more easily with people from diverse backgrounds, thereby laying a solid foundation for their future life and career development. In the process of students learning multiple languages, the learning of the mother tongue is extremely important. Many countries emphasize the importance of mother tongue education. Therefore, the Nurturing Early Learners – A Curriculum Framework for Kindergartens in Singapore: Guidelines for Teaching Chinese in Preschool, which integrates content related to the mother tongue curriculum and teaching into the overall framework, expands the scope of the “Language and Literacy” domain to include mother tongue and local cultural elements. The preschool stage is a critical period for young children to learn their mother tongue. Preschool teachers need to reflect on the learning aims and objectives of mother tongue education. Through this discussion, it is hoped to gain a deeper understanding of mother tongue education among young children and foster an element of culture in Singapore’s preschool education.